(untitled) (Research, Society and Development, 2022)
Objective: To identify the know undergraduate’s knowledge regarding patient safety during a supervised internship in a university hospital. Method: Exploratory, descriptive study of qualitative approach. 19 undergraduates from the nursing major’s 9° semester enrolled in the "Supervised internship in a general hospital and basic health units1. The information was collected from interviews guided by a semistructured instrument and analyzed according to the sentences proposed by Bardin (2011): 1. Pre-analysis; 2. Material exploration; 3. Results treatment. The study was approved by the Research Ethics Committee – Opinion No. 5.324.610. Results: The undergraduates, at the beginning of the internship, had very limited knowledge regarding patient safety, acquiring it during the discipline and extracurricular activities, presenting significant evolution relating to the subject along the internship. Conclusion: The activities developed during the period allowed the students a better judgment about the protocols implemented in the hospital and their importance to assistance quality. The study’s relevance and scientific contribution are expected found in the possibility of incorporating the data to develop student qualifications with the acquired knowledge about patient safety leading them to act multidisciplinary, aiming for an improvement in assistance quality.